Analysis of Damage and Repairs to the Transmission Part of the Komatsu Type GD825-2 Grader Unit - Wilarso, Wilarso; Bayu Idiyanto; Awang Surya; Hilman Sholih (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2024)
The Plant Rebuild Center, owned by PT. X, must raise quality to meet customer expectations and fulfill field needs. According to customer warranty claims in 2022, oil leaks in the transmission control valves of GD825-2 type units—11 in total—are the most common cause. This research's operational goal is to identify the source of the most damage to transmission components, particularly in Komatsu GD 825-2 units, so that corrective action may be taken and the effects can be monitored. At PT X's Plant Rebuild Center, corrective measures were implemented and standard operating procedures were created to serve as a guide for rebuilding Komatsu GD 825-2 unit transmission components. The analytical approach applies five why analyses. The findings show that oil leaks in the transmission control valve are the most common cause of damage. The engineering techniques used to achieve this improvement included duplicating the sleeve using the manufacturer's standard reference and altering the o-ring seat height during the semi-finishing stage before measuring and cutting during the finishing process. This resulted in the surfaces of the sleeve and transmission housing being identical. Work Instructions (INK) for installing the GD825-2 unit transmission control valve and a Checksheet for the GD825-2 type Grader unit transmission assembly have been developed as Standard Operating Procedures (SOPs)